2023
DOI: 10.1002/bmc.5564
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination and quality evaluation of 16 compounds in Ligustri Lucidi Fructus covering different regions and processed products using ultra‐high‐performance liquid chromatography‐mass spectrometry

Abstract: A quantitative analysis method and a chemical pattern recognition method were developed to evaluate raw Ligustri Lucidi Fructus (LLF) from different regions and different processed products. In this study, a comprehensive strategy using ultra‐high‐performance liquid chromatography‐mass spectrometry quantitative analysis method was established for the simultaneous determination of 16 components in 47 batches of LLF covering 19 regions belonging to 8 provinces and 24 batches of different processed products (stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a previous study [24], it was shown that the quality of raw LLF in central and northern regions including Shaanxi, Shandong, and Henan provinces was better than in southern regions. Herein, three biological replicates of each sample were harvested in parallel every month, collected from Xi'an (33°39′ N, 107°40′ E), Shaanxi Province in 9 months (the whole growth period from July to March of the next year in Xi'an, a total of 9 months) as the research objects, shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study [24], it was shown that the quality of raw LLF in central and northern regions including Shaanxi, Shandong, and Henan provinces was better than in southern regions. Herein, three biological replicates of each sample were harvested in parallel every month, collected from Xi'an (33°39′ N, 107°40′ E), Shaanxi Province in 9 months (the whole growth period from July to March of the next year in Xi'an, a total of 9 months) as the research objects, shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%